PENGARUH MOTIVASI KERJA DAN SELF EFFICACY TERHADAP PRESTASI KERJA DOSEN (Studi pada Dosen Universitas Atma Jaya Yogyakarta) - Andono Budi Seputro; Prayekti Prayekti; Jajuk Herawati (MANAJEMEN DEWANTARA, 2019)
This study aims to determine the effect of motivation on work performance, knowing the effect of self efficacy on work performance and knowing the effect of work motivation and self efficacy together on work performance. This type of research is correlational. The population in this study was the lectures at Atma Jaya Yogyakarta University. The sample used in this study was 76 respondents. The sampling technique uses purposive sampling. The technique used in data collection is a questionnaire. The data analysis technique used is multiple regression analysis. To find out the effect simultaneously used the F test, and to determine the effect partially used the t test. The results showed that motivation partially influences the work performance of lecturers, self efficacy partially influences the work performance of the lecturer, motivation and self efficacy simultaneously influence the work performance of the lecturer.Keywords: motivation, self efficacy, work performance